Genetic associations with personality and mental toughness profiles of English academy football players: An exploratory study - McAuley, A. B.; Hughes, D. C.; Tsaprouni, L. G.; Varley, I.; Suraci, B.; Baker, J.; Herbert, A. J.; Kelly, A. L. (Psychology of Sport and Exercise, 2022)
Psychological characteristics influence the performance of youth football players and are significant predictors of development and success at adulthood. Although genetic factors may explain a considerable portion of inter-individual differences in psychological traits, psychogenetic research in football is scarce. As such, the purpose of this study was to examine the association of ten single nucleotide polymorphisms (SNPs) with personality and mental toughness profiles of academy football players. Seventy-three male under-12 to under-18 football players from a Category 3 English academy were genotyped for ten SNPs. Personality and mental toughness were assessed using a 50-item IPIP Big Five personality traits questionnaire and the Mental Toughness Index, respectively. Simple linear regression was used to analyse individual SNP associations with personality dimensions and mental toughness, whereas both unweighted and weighted total genotype scores (TGSs; TWGSs) were computed to measure the combined influence of all SNPs. There was a significant association between DRD3 (rs167771) and agreeableness (p = .043), where A/A homozygotes scored higher than G allele carriers. TGSs and/or TWGSs were significantly correlated with mental toughness and each personality dimension except openness, explaining between 3 and 17% of the variance. The results of this study suggest psychological characteristics of youth football players are partly determined by genetic factors.